Web, value and labour. (1st July 2013) - ,
Abstract : This paper challenges the dominant discourse that the Internet is changing the economy dramatically. In a context where digitised value creation is spreading, it critiques the economically- inspired diagnosis of a fundamentally changed Internet economy from a sociological perspective and establishes that the available economic data do not justify this prognosis. It next critically discusses current research into Web-related value creation, starting with a classic and generic definition of the concept. It then suggests a new conceptual approach to the relationship between Web and value, drawing a clear disticntion between value generation and value realisation and differentiating both along the offline/online and commodities/commons dimensions. By means of these steps, the paper concludes that human labour remains the key source both of value origination and of value realisation processes, even in the Web 2.0 Internet economy.